2021
DOI: 10.21577/0103-5053.20210096
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life of Bioactive Compounds from Acerola Pulp (Malpighia spp.) through Freeze-Drying and Microencapsulation

Abstract: Acerola is a tropical fruit with a large industrial and commercial appeal due to its organoleptic qualities and bioactive compound-rich nature. Thus, as bioactive compounds (BC) stability is of great interest in the food industry, assessment of preserving techniques to prolong shelf life has become imperative. Hence, the purpose of this study was to evaluate how storage affects BC conservation in microencapsulated and lyophilized acerola pulps over 180 days. For this matter, antioxidant tests, physical-chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Saqueti et al had used freeze drying to extend the shelf life of acerola pulp. The encapsulation technique preserved the biologically active compounds in acerola pulp for more than180 days (Saqueti et al, 2021).…”
Section: Other Studies Of Spray‐ and Freeze‐dried Productsmentioning
confidence: 99%
“…Saqueti et al had used freeze drying to extend the shelf life of acerola pulp. The encapsulation technique preserved the biologically active compounds in acerola pulp for more than180 days (Saqueti et al, 2021).…”
Section: Other Studies Of Spray‐ and Freeze‐dried Productsmentioning
confidence: 99%
“…Moreover, the results indicated that microencapsulation outperformed lyophilization in preserving the desired compounds in Acerola pulp over a span of 6 months, as evidenced by the superior BCPs content in the microencapsulated samples. These results highlight the potential of microencapsulation as an attractive option for the food industry (129,130).…”
Section: Microencapsulation Improves Bioflavonoids' Shelf-lifementioning
confidence: 65%
“…The literature has numerous techniques for drying acerola pulps. The freeze-drying preserved the pulp ascorbic acid presented in an acerola pulp [11]. The effect of hot air, vacuum drying, and freeze-drying was investigated on acerola pulp quality attributes, including its active compounds.…”
Section: Introductionmentioning
confidence: 99%